2013
DOI: 10.1039/c3nr02560h
|View full text |Cite
|
Sign up to set email alerts
|

An atomistic view of the interfacial structures of AuRh and AuPd nanorods

Abstract: In this work we address the challenge of furthering our understanding of the driving forces responsible for the metal-metal interactions in industrially relevant bimetallic nanocatalysts, by taking a comparative approach to the atomic scale characterization of two core-shell nanorod systems (AuPd and AuRh). Using aberration-corrected scanning transmission electron microscopy, we show the existence of a randomly mixed alloy layer some 4-5 atomic layers thick between completely bulk immiscible Au and Rh, which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 40 publications
3
43
0
3
Order By: Relevance
“…[4][5][6][7] Using either chemical or physical preparation techniques, they showed that Au tends to cover the Rh surface. Using scanning transmission electron microscopy (STEM), Chantry et al 8,9 highlighted the tendency of Rh either to deposit in an uneven way on Au nanorods and/or to form mixed alloy layers at the topmost surface depending on kinetic issues during the formation of such nanostructures. Similarly, Sneed et al 10 observed the formation of island overgrowth of Rh onto Au nanocubes or octahedra.…”
mentioning
confidence: 99%
“…[4][5][6][7] Using either chemical or physical preparation techniques, they showed that Au tends to cover the Rh surface. Using scanning transmission electron microscopy (STEM), Chantry et al 8,9 highlighted the tendency of Rh either to deposit in an uneven way on Au nanorods and/or to form mixed alloy layers at the topmost surface depending on kinetic issues during the formation of such nanostructures. Similarly, Sneed et al 10 observed the formation of island overgrowth of Rh onto Au nanocubes or octahedra.…”
mentioning
confidence: 99%
“…4, to AuRh nanorods synthesised using a seed-mediated sequential growth method via a wet chemical route. The main results have been reported in two recent publications [51,80]. Figure 5 shows EDX maps of Au and Rh overlaid on the same image.…”
Section: Characterisation Of Interfacial Structures Of Aurh and Aupd mentioning
confidence: 68%
“…Where the sample is of uniform thickness, HAADF image contrast variation can be directly related to sample elemental variation. Figure 3 shows a typical HAADF image of segregated AuPd nanorods [51], demonstrating a clear difference in image intensity between the Au core (Z ¼ 79) and the Pd shell (Z ¼ 46).…”
Section: Imagingmentioning
confidence: 98%
See 1 more Smart Citation
“…Especially, bimetallic nanoparticles, composed of two kinds of metal elements, have attracted persistently substantial attention not only because of their combining properties of each constituent metal but also because of their additional peculiar properties not observed in their monometallic counterparts [4,10,11].…”
Section: Introductionmentioning
confidence: 99%